New faunistic records of Gelechiid-Moths from the Southern Siberia with description of three new species (Lepidoptera). - Bidzilya, Oleksiy V. (Contributions to Entomology = Beiträge zur Entomologie, 2000)
Xystophora kostjuki sp. n., Agonachaetia tuvella sp. n. (Russia, Tuva Republic), and Chionodes borzella sp. n. (Russia, Chita region) are described. The combination Monochroa rufulella (Snellen, 1884), comb. n. is proposed. A distributional list with 22 species, including three new records (Monochroa moyses Uffen, M. hornigi Stgr., Daltopora felixi Pov.) for the Russia Federation, is presented. Keywords Lepidoptera, Gelechiidae, new species, Southern Siberia. Nomenclatural Acts tuvella Bidzilya, 2000 (Agonochaetia), spec. n. borzella Bidzilya, 2000 (Chionodes), spec. n. rufulella (Snellen, 1884) (Monochroa), comb. n. hitherto Xystophora rufulella kostjuki Bidzilya, 2000 (Xystophora), spec. n.